What dose of caffeine to use: Acute effects of 3 doses of caffeine on muscle endurance and strength - Grgic, J.; Sabol, F.; Venier, S.; Mikulic, I.; Bratkovic, N.; Schoenfeld, B. J.; Pickering, C.; Bishop, D. J.; Pedisic, Z.; Mikulic, P. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To explore the effects of 3 doses of caffeine on muscle strength and muscle endurance. Methods: Twenty-eight resistance-trained men completed the testing sessions under 5 conditions: no-placebo control, placebo control, and with caffeine doses of 2, 4, and 6 mg/kg. Muscle strength was assessed using the 1-repetition-maximum test; muscle endurance was assessed by having the participants perform a maximal number of repetitions with 60% 1-repetition maximum. Results: In comparison with both control conditions, only a caffeine dose of 2 mg/kg enhanced lower-body strength (d=0.13-0.15). In comparison with the no-placebo control condition, caffeine doses of 4 and 6 mg/kg enhanced upper-body strength (d=0.07-0.09) with a significant linear trend for the effectiveness of different doses of caffeine (P=.020). Compared with both control conditions, all 3 caffeine doses enhanced lower-body muscle endurance (d=0.46-0.68). For upper-body muscle endurance, this study did not find significant effects of caffeine. Conclusions: This study revealed a linear trend between the dose of caffeine and its effects on upper-body strength. The study found no clear association between the dose of caffeine and the magnitude of its ergogenic effects on lower-body strength and muscle endurance. From a practical standpoint, the magnitude of caffeine`s effects on strength is of questionable relevance. A low dose of caffeine (2 mg/kg)—for an 80-kg individual, the dose of caffeine in 1-2 cups of coffee—may produce substantial improvements in lower-body muscle endurance with the magnitude of the effect being similar to that attained using higher doses of caffeine.